Peningkatan Pengetahuan Siswa Mengenai Kanker Payudara di SMA Negeri 1 Majalengka - Lestari Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
It is necessary to increase understanding of breast cancer as an initial bridge to increase awareness and ultimately contribute to reducing incidence and mortality. Community service carried out by the Anatomic Pathology Department of FK UGJ was held at SMAN 1 Majalengka, attended by 58 class representatives. Starting with filling out a pretest, then providing education about breast cancer and ending with a post test. The pretest and posttest results were then assessed and grouped into three categories, namely good (8-10), moderate (6-7), and poor (1-5). There was a significant increase in the pretest and posttest results, namely the good category from 43% to 97%, a significant decrease for the moderate and poor categories, namely 38% to 3% and 19% to 0% respectively. The conclusion of the results of this community service was proven to increase students' knowledge regarding breast cancer.